(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2020)
Workers are calling for a new psychological contract in which power differences are less asymmetrical and underrepresented voices are heard. In this context, the present study identifies the gaps between the three organizational hierarchical levels (strategic, executive and operational) with a focus on power asymmetries. Employing the case studies methodology, Denison’s (1990) instrument is applied to measure the four dimensions (Adaptability, Involvement, Mission and Consistency) of organizational culture at a supermarket located in northern Chile that is part of a leading chain regionally and nationally. Information was collected through 163 surveys and analyzed using nonparametric statistics. The results reveal a high correlation between hierarchal levels and the dimensions of organizational culture. However, in four particular sub-dimensions (empowerment, capability development, core values, and agreement), the operational level feels that the higher hierarchal levels impose their power. As well as affecting their motivation and commitment, this compels the lower-level workers to take actions–in which informal power plays a key role–to reduce asymmetries. In sum, the relationship explored in this study between organizational culture, hierarchal levels and power is one that future research should examine in greater depth.